Popular Culture as an Educative Teaching Tool in the Elementary Classroom - Romeo, Raquel; Ryan, Thomas (International Journal of Learning and Instruction (IJLI), 2023)
The purpose of this research was to investigate popular culture as a means to educate in the elementary school classroom. Using secondary research in education and cultural studies, we investigated how teachers can use popular media to enhance student learning and develop critical media literacy skills. Findings revealed popular culture is a helpful teaching tool in elementary school classrooms. Knowledge of popular culture does not impede education but is a large part of students"™ literacy practices. By embracing popular culture, students develop the literacies needed to navigate 21st century schools and engage in critical pedagogy. Further studies are needed to establish the practical ways elementary school teachers can use popular texts in their classrooms and overcome literacy challenges they may face.